2020
DOI: 10.1186/s12882-020-1695-1
|View full text |Cite
|
Sign up to set email alerts
|

Enabling good outcomes in older adults on dialysis: a qualitative study

Abstract: Background: Older patients on dialysis may not have optimal outcomes, particularly with regards to quality of life. Existing research is focused mainly on survival, with limited information about other outcomes. Such information can help in shared decision-making around dialysis initiation; it can also be used to improve outcomes in patients established on dialysis. We used qualitative research methods to explore patient perspectives regarding their experience and outcomes with dialysis. Methods: Semi-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…Whilst there is usually an element of choice to HD nonadherence, it is important to recognise the impact such demanding care can have on a patient and how it can fracture the providerpatient relationship. Patients who do not engage in care the way their nephrologists expect are often viewed in a condescending way [28], which can lead to patient anger [29]. The inherent vulnerability of patients does not necessarily absolve them from wrongdoing [30] but must be appreciated as potentially contributing to adherence issues.…”
Section: Mr B (1): Missed Sessions and Emergency Presentation Box 3 Mr Bmentioning
confidence: 99%
“…Whilst there is usually an element of choice to HD nonadherence, it is important to recognise the impact such demanding care can have on a patient and how it can fracture the providerpatient relationship. Patients who do not engage in care the way their nephrologists expect are often viewed in a condescending way [28], which can lead to patient anger [29]. The inherent vulnerability of patients does not necessarily absolve them from wrongdoing [30] but must be appreciated as potentially contributing to adherence issues.…”
Section: Mr B (1): Missed Sessions and Emergency Presentation Box 3 Mr Bmentioning
confidence: 99%
“…Social interaction support showed a positively predictive effect on psychological resilience, possibly due to the fact that individuals who reported greater support received in positive social interactions would have higher levels of self-efficacy ( 43 ) and more resources to cope with stress and the burden of illness ( 44 ). Qualitative studies found that positive social interactions gives hemodialysis patients a sense of meaning in life and hope for the future ( 45 ), as well as positive emotional experiences and self-worth ( 46 ). Thus, nursing interventions focused on promoting positive social interaction support as appropriate and directly or indirectly mobilizing or expanding the social network of the patient may be an effective strategy to improve the psychological resilience of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a summary of qualitative studies, 21 our participants described developing a need for assistance from others, the emotional impact of life receiving dialysis, and the value of relationship and communication with their providers. In 2 studies specific to older adults receiving dialysis, 22 , 23 support with medications or mobility impairment were identified as key needs. Our study builds on this existing knowledge by incorporating dialysis personnel perspectives.…”
Section: Discussionmentioning
confidence: 99%